2023
DOI: 10.1002/cjp2.324
|View full text |Cite
|
Sign up to set email alerts
|

NTRK gene aberrations in triple‐negative breast cancer: detection challenges using IHC, FISH, RT‐PCR, and NGS

Abstract: Triple‐negative breast cancer (TNBC) is usually an aggressive disease with a poor prognosis and limited treatment options. The neurotrophic tyrosine receptor kinase (NTRK) gene fusions are cancer type‐agnostic emerging biomarkers approved by the Food and Drug Administration (FDA), USA, for the selection of patients for targeted therapy. The main aim of our study was to investigate the frequency of NTRK aberrations, i.e. fusions, gene copy number gain, and amplification, in a series of TNBC using different meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The most frequently mutated amino acid sites in NTRK1/2/3 were G169R, A268V, and R153L/Q, respectively. Prior research has indicated that non-fusion NTRK alterations, such as mutations and amplifications, are associated with the response to NTRK inhibitors and their therapeutic efficacy ( Okamura et al, 2018 ; Amatu et al, 2019 ; Zito Marino et al, 2023 ). In particular, mutations at the G595R and G667C sites of NTRK1 , and at G696A and G623R of NTRK3 , have been associated with the acquisition of resistance to first-generation NTRK inhibitors, possibly due to the fact that these point mutations alter the three-dimensional conformation of the kinase’s structural domains, thereby reducing or abolishing binding to the inhibitors ( Russo et al, 2016 ; Drilon et al, 2017 ; Somwar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently mutated amino acid sites in NTRK1/2/3 were G169R, A268V, and R153L/Q, respectively. Prior research has indicated that non-fusion NTRK alterations, such as mutations and amplifications, are associated with the response to NTRK inhibitors and their therapeutic efficacy ( Okamura et al, 2018 ; Amatu et al, 2019 ; Zito Marino et al, 2023 ). In particular, mutations at the G595R and G667C sites of NTRK1 , and at G696A and G623R of NTRK3 , have been associated with the acquisition of resistance to first-generation NTRK inhibitors, possibly due to the fact that these point mutations alter the three-dimensional conformation of the kinase’s structural domains, thereby reducing or abolishing binding to the inhibitors ( Russo et al, 2016 ; Drilon et al, 2017 ; Somwar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Light et al reported that NTRK1/3 were highly expressed in neuroblastoma patients with a better prognosis, whereas NTRK2 was highly expressed in neuroblastoma patients with a poor prognosis ( Light et al, 2012 ). Additionally, in 83 clinical samples of triple-negative breast cancers, NTRK1/2/3 were found to exhibit varying degrees of copy number gain and amplification ( Zito Marino et al, 2023 ). However, these aforementioned studies are limited by focusing on specific cancer types and small sample sizes, highlighting the critical need for comprehensive analyses across multiple tumor types to investigate their functions.…”
Section: Introductionmentioning
confidence: 99%
“…TRK expression was detected in 133/898 (15%) NSCLCs; 120 of these carcinomas were available for NGS analysis, with only two instances of NTRK fusions eventually confirmed. Zito Marino et al [ 42 ] revealed pan-TRK IHC positivity in 16 out of 83 triple-negative breast malignancies; however, none of these samples carried translocation upon NGS. Vingiani et al [ 43 ] analyzed the collection composed of several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, solid tumors exhibit a heightened prevalence of CNAs, emphasizing their significance in the context of solid tumor biology [3]. While various laboratory-based methods, such as multiplex ligation-dependent probe amplification (MLPA) [4], microarray-based comparative genomic hybridization (aCGH) [5], SNP microarrays [6], RNA sequencing [7], fluorescence in situ hybridization (FISH) [8] and PCR-based approaches [9], facilitate CNA detection, they are often limited by factors like restricted coverage and resolution, tissue consumption, labor intensiveness, low throughput, and high cost [10]. Recent progress in next-generation sequencing (NGS) technologies has facilitated the concurrent identification of targeted CNAs and somatic mutations by utilizing a panel-based NGS approach.…”
Section: Introductionmentioning
confidence: 99%